2002
DOI: 10.1210/en.2002-220291
|View full text |Cite
|
Sign up to set email alerts
|

Does Cortisol Mediate Endotoxin-Induced Inhibition of Pulsatile Luteinizing Hormone and Gonadotropin-Releasing Hormone Secretion?

Abstract: Bacterial endotoxin (lipopolysaccharide), a commonly used model of immune/inflammatory stress, inhibits reproductive neuroendocrine activity and concurrently induces a profound stimulation of the hypothalamo-pituitary-adrenal axis. We employed two approaches to test the hypothesis that enhanced secretion of cortisol mediates endotoxin-induced suppression of pulsatile GnRH and LH secretion in the ovariectomized ewe. First, we mimicked the endotoxin-induced increase in circulating cortisol by delivering the gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 42 publications
7
38
0
1
Order By: Relevance
“…Finally, we are puzzled why psychosocial stress enhanced GnRH pulse frequency in experiment 2 but not in experiment 1. Although we have no explanation for this, it is noteworthy that another stress type, immune-inflammatory stress (endotoxin), has caused an increase in GnRH pulse frequency in sheep, but this effect, too, was inconsistent across studies (5,16,17). Possibly related to this, endotoxin stimulates CRH secretion in sheep (38,39), and central delivery of CRH in sheep increased LH pulse frequency in some studies, but not in others (40 -42).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, we are puzzled why psychosocial stress enhanced GnRH pulse frequency in experiment 2 but not in experiment 1. Although we have no explanation for this, it is noteworthy that another stress type, immune-inflammatory stress (endotoxin), has caused an increase in GnRH pulse frequency in sheep, but this effect, too, was inconsistent across studies (5,16,17). Possibly related to this, endotoxin stimulates CRH secretion in sheep (38,39), and central delivery of CRH in sheep increased LH pulse frequency in some studies, but not in others (40 -42).…”
Section: Discussionmentioning
confidence: 82%
“…For example, psychosocial stress increases circulating levels of glucocorticoids and inhibits pulsatile LH secretion (1)(2)(3)(4). Recent studies in ovariectomized sheep have demonstrated that a stress-like elevation of plasma cortisol decreases pulsatile LH secretion in the absence of stress and that this occurs via suppression of pituitary responsiveness to GnRH (5)(6)(7). This effect of cortisol, which reflects a direct action on the pituitary and mediation by the type II glucocorticoid receptor (GR), occurs without concurrent inhibition of pulsatile GnRH secretion (6,8,9).…”
mentioning
confidence: 99%
“…There are few reports of the effects of stress on GnRH secretion [1], although the pulsatile secretion of LH is taken to reflect GnRH secretion, due to the tight coupling of the secretion of these two hormones [22]. Cortisol suppresses secretion of LH [23, 24], which provides one mechanism by which the reproductive system can be affected by stress, but the central circuitry involved is not defined. Whether this is due to a direct input to GnRH cells from stress-activated neuronal systems, or to input to the region of the brain in which GnRH cells are found remains to be fully deciphered.…”
Section: Introductionmentioning
confidence: 99%
“…371,372 Thus acute treatments with glucocorticoids have little effect on episodic LH secretion in rats, monkeys, and humans. Cortisol does act at the pituitary to suppress LH pulse amplitude in ewes 373 ; this action is not required for the inhibition of episodic LH secretion by endotoxin, 374 but may play an important role in the effects of psychosocial stress. 375,376 Moreover, cortisol clearly suppresses LH pulse frequency during the follicular phase of the ovine estrous cycle, 377 so sheep may be one species in which glucocorticoids have important inhibitory effects on GnRH secretion.…”
Section: Stressorsmentioning
confidence: 99%